9.6k views
4 votes
Prove the following integration formula:


\displaystyle \int e^(au)\sin(bu)\, du=(e^(au))/(a^2+b^2)(a\sin(bu)-b\cos(bu))+C

User Rhellem
by
4.3k points

2 Answers

4 votes

Answer:

See Explanation.

General Formulas and Concepts:

Pre-Algebra

  • Distributive Property
  • Equality Properties

Algebra I

  • Combining Like Terms
  • Factoring

Calculus

  • Derivative 1:
    (d)/(dx) [e^u]=u'e^u
  • Integration Constant C
  • Integral 1:
    \int {e^x} \, dx = e^x + C
  • Integral 2:
    \int {sin(x)} \, dx = -cos(x) + C
  • Integral 3:
    \int {cos(x)} \, dx = sin(x) + C
  • Integral Rule 1:
    \int {cf(x)} \, dx = c \int {f(x)} \, dx
  • Integration by Parts:
    \int {u} \, dv = uv - \int {v} \, du
  • [IBP] LIPET: Logs, Inverses, Polynomials, Exponents, Trig

Explanation:

Step 1: Define Integral


\int {e^(au)sin(bu)} \, du

Step 2: Identify Variables Pt. 1

Using LIPET, we determine the variables for IBP.

Use Int Rules 2 + 3.


u = e^(au)\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ dv = sin(bu)du\\du = ae^(au)du \ \ \ \ \ \ \ \ \ v = (-cos(bu))/(b)

Step 3: Integrate Pt. 1

  1. Integrate [IBP]:
    \int {e^(au)sin(bu)} \, du = (-e^(au)cos(bu))/(b) - \int ({ae^(au) \cdot (-cos(bu))/(b) }) \, du
  2. Integrate [Int Rule 1]:
    \int {e^(au)sin(bu)} \, du = (-e^(au)cos(bu))/(b) + (a)/(b) \int ({e^(au)cos(bu)}) \, du

Step 4: Identify Variables Pt. 2

Using LIPET, we determine the variables for the 2nd IBP.

Use Int Rules 2 + 3.


u = e^(au)\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ dv = cos(bu)du\\du = ae^(au)du \ \ \ \ \ \ \ \ \ v = (sin(bu))/(b)

Step 5: Integrate Pt. 2

  1. Integrate [IBP]:
    \int {e^(au)cos(bu)} \, du = (e^(au)sin(bu))/(b) - \int ({ae^(au) \cdot (sin(bu))/(b) }) \, du
  2. Integrate [Int Rule 1]:
    \int {e^(au)cos(bu)} \, du = (e^(au)sin(bu))/(b) - (a)/(b) \int ({e^(au) sin(bu)}) \, du

Step 6: Integrate Pt. 3

  1. Integrate [Alg - Back substitute]:
    \int {e^(au)sin(bu)} \, du = (-e^(au)cos(bu))/(b) + (a)/(b) [(e^(au)sin(bu))/(b) - (a)/(b) \int ({e^(au) sin(bu)}) \, du]
  2. [Integral - Alg] Distribute Brackets:
    \int {e^(au)sin(bu)} \, du = (-e^(au)cos(bu))/(b) + (ae^(au)sin(bu))/(b^2) - (a^2)/(b^2) \int ({e^(au) sin(bu)}) \, du
  3. [Integral - Alg] Isolate Original Terms:
    \int {e^(au)sin(bu)} \, du + (a^2)/(b^2) \int ({e^(au) sin(bu)}) \, du= (-e^(au)cos(bu))/(b) + (ae^(au)sin(bu))/(b^2)
  4. [Integral - Alg] Rewrite:
    ((a^2)/(b^2) +1)\int {e^(au)sin(bu)} \, du = (-e^(au)cos(bu))/(b) + (ae^(au)sin(bu))/(b^2)
  5. [Integral - Alg] Isolate Original:
    \int {e^(au)sin(bu)} \, du = ((-e^(au)cos(bu))/(b) + (ae^(au)sin(bu))/(b^2))/((a^2)/(b^2) +1)
  6. [Integral - Alg] Rewrite Fraction:
    \int {e^(au)sin(bu)} \, du = ((-be^(au)cos(bu))/(b^2) + (ae^(au)sin(bu))/(b^2))/((a^2)/(b^2) +(b^2)/(b^2) )
  7. [Integral - Alg] Combine Like Terms:
    \int {e^(au)sin(bu)} \, du = ((ae^(au)sin(bu)-be^(au)cos(bu))/(b^2) )/((a^2+b^2)/(b^2) )
  8. [Integral - Alg] Divide:
    \int {e^(au)sin(bu)} \, du = (ae^(au)sin(bu) - be^(au)cos(bu))/(b^2) \cdot (b^2)/(a^2 + b^2)
  9. [Integral - Alg] Multiply:
    \int {e^(au)sin(bu)} \, du = (1)/(a^2+b^2) [ae^(au)sin(bu) - be^(au)cos(bu)]
  10. [Integral - Alg] Factor:
    \int {e^(au)sin(bu)} \, du = (e^(au))/(a^2+b^2) [asin(bu) - bcos(bu)]
  11. [Integral] Integration Constant:
    \int {e^(au)sin(bu)} \, du = (e^(au))/(a^2+b^2) [asin(bu) - bcos(bu)] + C

And we have proved the integration formula!

User Artemis
by
5.7k points
5 votes

Prove:
\displaystyle \int e^a^u sin(bu)\ du = (e^a^u)/(a^2+b^2) (a \ sin(bu) - b \ cos(bu)) + C

Integration by parts formula:
\displaystyle \int udv = uv - \int vdu

Find u, du, v, and dv for this function:
\displaystyle \int e^a^u sin(bu)


  • \displaystyle u =e^a^u \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ v = -(cos(bu))/(b) \\ du=ae^a^u \ du \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ dv = sin(bu) \ du

Plug these values into the IBP formula.


  • \displaystyle \int e^a^u sin(bu) \ du = e^a^u \cdot (-cos(bu))/(b) - \int -(cos(bu))/(b) \cdot ae^a^u \ du

Multiply and simplify the factors. Factor the negative out of the integral.


  • \displaystyle \int e^a^u sin(bu) \ du = -(e^a^u cos(bu))/(b) +\int (a \ cos(bu) \ e^a^u)/(b) \ du

Factor out a/b from the integral.


  • \displaystyle \int e^a^u sin(bu) \ du = -(e^a^u cos(bu))/(b) + (a)/(b) \int cos(bu) \ e^a^u \ du

Now we are going to apply IBP to the function:
\displaystyle \int cos(bu) \ e^a^u . Find u, du, v, and dv for this function.


  • \displaystyle u =e^a^u \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ v = (sin(bu))/(b) \\ du=ae^a^u \ du \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ dv = cos(bu) \ du

Plug these values into the IBP formula.


  • \displaystyle \int e^a^u cos(bu) \ du = e^a^u \cdot (sin(bu))/(b) - \int (sin(bu))/(b) \cdot ae^a^u \ du

Multiply and simplify the factors.


  • \displaystyle \int e^a^u cos(bu) \ du = (e^a^u \ sin(bu))/(b) - \int (a \ sin(bu)\ e^a^u)/(b) \ du

Factor out a/b from the integral.


  • \displaystyle \int e^a^u cos(bu) \ du = (e^a^u \ sin(bu))/(b) - (a)/(b) \int sin(bu)\ e^a^u} \ du

Notice that we have the same integral we started with. Let's plug this integral into the original IBP we did.


  • \displaystyle \int e^a^u sin(bu) \ du = -(e^a^u cos(bu))/(b) + (a)/(b) \big{[ }(e^a^u sin(bu))/(b) - (a)/(b) \int sin(bu) \ e^a^u \ du \big{]}}

Distribute a/b inside the parentheses.


  • \displaystyle \int e^a^u sin(bu) \ du = -(e^a^u cos(bu))/(b) + (a \ e^a^u sin(bu))/(b^2) - (a^2)/(b^2) \int sin(bu) \ e^a^u \ du

Factor 1/b out of the right side of the equation.


  • \displaystyle \int e^a^u sin(bu) \ du = (1)/(b)\big{[} -e^a^u cos(bu)+ a \big{(}(e^a^u sin(bu))/(b) \big{)} - (a^2)/(b) \int sin(bu) \ e^a^u \ du \big{]}

Multiply both sides by b to get rid of 1/b.


  • \displaystyle b \int e^a^u sin(bu) \ du = -e^a^u cos(bu)+ a \big{(}(e^a^u sin(bu))/(b) \big{)} - (a^2)/(b) \int sin(bu) \ e^a^u \ du

Add the integral to both sides of the equation.


  • \displaystyle b \int e^a^u sin(bu) \ du + (a^2)/(b) \int sin(bu) \ e^a^u \ du= -e^a^u cos(bu)+ a \big{(}(e^a^u sin(bu))/(b) \big{)}

Factor the integral on the left side.


  • \displaystyle \int e^a^u sin(bu) \ du \ \big{(} b + (a^2)/(b) \big{)}= -e^a^u cos(bu)+ a \big{(}(e^a^u sin(bu))/(b) \big{)}


\displaystyle \big{(}b+(a^2)/(b) \big{)} = (b^2+a^2)/(b), so we can multiply both sides of the equation by
\displaystyle (b)/(a^2+b^2).


  • \displaystyle \int e^a^u sin(bu) \ du = -e^a^u cos(bu)+ a \big{(}(e^a^u sin(bu))/(b) \big{)} \big{(} (b)/(a^2+b^2) \big{)}

Simplify the equation before multiplying everything by
\displaystyle (b)/(a^2+b^2).


  • \displaystyle \int e^a^u sin(bu) \ du = \big{(}(-e^a^u cos(bu) \ b + a \ e^a^u sin(bu))/(b) \big{)} \big{(} (b)/(a^2+b^2) \big{)}

Multiply the two factors together. Notice that the two b's in the denominator and numerator, respectively, cancel out. We are left with:


  • \displaystyle \int e^a^u sin(bu) \ du = \big{(}(-e^a^u cos(bu) \ b + a \ e^a^u sin(bu))/(a^2+b^2) \big{)}

Factor
\displaystyle e^a^u from the numerator.


  • \displaystyle \int e^a^u sin(bu) \ du = \big{(}(e^a^u( -b \ cos(bu) \ + a \ sin(bu))/(a^2+b^2) \big{)}

Split the numerator and denominator to make it appear the same as the original question.


  • \displaystyle \int e^a^u sin(bu) \ du = (e^a^u)/(a^2+b^2) \big{(} a \ sin(bu) - b \ cos(bu) \big{)}

Since we are taking the integral of something, we can add a +C at the end to complete the problem.


  • \displaystyle \int e^a^u sin(bu) \ du = (e^a^u)/(a^2+b^2) \big{(} a \ sin(bu) - b \ cos(bu) \big{)} + C

This is equivalent to the proof that we are given, therefore, we proved the integral correctly.

User Chrisblo
by
5.3k points